Islamic narrative and authority in Southeast Asia: from the 16th to the 21st century - Gibson, Thomas (Contemporary anthropology of religion, 2007)
Introduction : symbolic knowledge and authority in complex societies -- The ruler as perfect man in Southeast Asia, 1500-1667 -- Cosmopolitan Islam in South Sulawesi, 1640-1705 -- Islamic martyrdom and the Great Lord of the VOC, 1705-1988 -- Popular mysticism and the Colonial State, 1811-1936 -- Cosmopolitan piety and the late Colonial State, 1850-1950 -- Revolutionary Islam and the Nation-State, 1900-1965 -- Official Islam and the Developmental State, 1965-2004 -- Conclusion : narrative, ritual, and models of the self